Synthesis of Enantiomeric Aminoalkylcarbamoylphosphonates and Their Evaluation as Dual‐Action Anticancer MMP and Carbonic Anhydrase Inhibitors. Issue 4 (28th January 2015) - Veerendhar, Ainelly; Cohen, Shmuel; Frant, Julia; Supuran, Claudiu T.; Reich, Reuven; Breuer, Eli
ABSTRACT Carbamoylphosphonates (CPOs) have recently been identified as extracellular in vivo active inhibitors of the cancer and metastasis‐promoting extracellular enzymes, carbonic anhydrases (CAs) IX and XII, and matrix metalloproteinase‐2 (MMP‐2). This article describes the stereoselective synthesis and the evaluation of the biological properties of a pair of enantiomeric aminoalkylcarbamoylphosphonates, which have been enantioselectively synthesized from l‐serine, using functional group‐transformations. The structures of the enantiomeric products have been determined by X‐ray crystallography. The enantiomeric purities of compounds have been confirmed by chiral shift reagent NMR experiments and by circular dichroism. In vitro evaluation of the CPOs synthesized revealed that they possess micromolar IC50 inhibitory action against CAIX and CAXII. The two enantiomers as well as the racemic or optically inactive ones do not differ by any significant extent from previously reported CPOs' CA inhibitory values. On the other hand, MMPs inhibitory activities are rather weak; only MMP‐2 showed a notable IC50 value.